Bibliometric Analysis of Solar and Wind Renewable Energy - Loso Judijanto; Nanny Mayasari (Westscience Press, 2026)
This study conducts a bibliometric analysis of solar and wind renewable energy research to map its intellectual structure, thematic evolution, and global collaboration patterns. Using bibliometric visualization techniques, the study examines keyword co-occurrence, co-authorship networks, institutional collaboration, and country-level research distribution. The findings indicate that the field is strongly centered on core themes such as renewable energy systems, solar energy, and wind power, with significant emphasis on grid integration, optimization, and energy storage technologies. Emerging research trends highlight increasing attention toward hydrogen production, energy transition, sustainability, and policy-driven decarbonization strategies. The collaboration network analysis reveals that China, India, and the United States serve as dominant global research hubs, facilitating extensive international cooperation across Europe, Asia, and the Middle East. Institutional analysis further shows that engineering faculties remain the primary contributors, while interdisciplinary collaboration with economics and management domains is still developing.